2021
DOI: 10.3390/polym13111684
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin Monomers and Polymers for Drug Activity Enhancement

Abstract: Cyclodextrins (CDs) and cyclodextrin (CD)-based polymers are well-known complexing agents. One of their distinctive features is to increase the quantity of a drug in a solution or improve its delivery. However, in certain instances, the activity of the solutions is increased not only due to the increase of the drug dose but also due to the drug complexation. Based on numerous studies reviewed, the drug appeared more active in a complex form. This review aims to summarize the performance of CDs and CD-based pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 174 publications
(182 reference statements)
0
24
0
Order By: Relevance
“…However, several of the studies reported showed a higher increase in concentration with CD-based polymers when compared to CD monomers, such as the case of KYNA [ 62 ], where the solubility increased 6.7-fold between CD monomers and polymers. This increase in solubility has been reported as an eventual increase in bioavailability [ 10 ]. For future uses, the degradation of bonds of CD-based polymers should be considered.…”
Section: Critical Overview Of the Capacity Toxicity And Current Status Of Cd-based Materialsmentioning
confidence: 80%
See 1 more Smart Citation
“…However, several of the studies reported showed a higher increase in concentration with CD-based polymers when compared to CD monomers, such as the case of KYNA [ 62 ], where the solubility increased 6.7-fold between CD monomers and polymers. This increase in solubility has been reported as an eventual increase in bioavailability [ 10 ]. For future uses, the degradation of bonds of CD-based polymers should be considered.…”
Section: Critical Overview Of the Capacity Toxicity And Current Status Of Cd-based Materialsmentioning
confidence: 80%
“…In general, the inclusion complex formation improves the apparent solubility of the drug, which increases its final concentration, even affecting the BaC structure and possibly its bioactivities [ 4 , 5 , 6 , 7 , 8 , 9 ]. However, other effects such as increased stability, controlled release or chiral separation occur when the inclusion complex is formed [ 10 ]. Finally, their uses as active agents (without a guess) are being also studied for different diseases or applications [ 3 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the light of the considerations made above, it is clear that CDs respond to the need to optimize treatments that already exist, making them more effective, stable and safe. Encapsulation of CDs has been demonstrated to be efficient in solving these kind of issues [ 8 , 118 ] while maintaining or even increasing the biological activity of these agents because they act as multifunctional excipients in that they are solubility enhancers, prevent drug–drug and drug–additive interactions within a formulation, eliminate unpleasant smells or tastes and reduce side effects [ 5 , 53 , 119 , 120 ]. Even their own activity as active drugs could promote possible synergetic capacities [ 116 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the intrinsic structure of CDs allows the synthesis and design of CD-based polymers with specific functions and assemblies [ 78 ]. This route is suitable to improve the properties and the activity of different active substances [ 27 , 79 ].…”
Section: Incorporation Of Active Substances In Polymeric Matrix Composites For Active Packaging Applicationsmentioning
confidence: 99%
“…To summarize, the most relevant studies regarding the use of cyclodextrin inclusion complexes (CICs) in active food packaging applications are listed in Table 4 . It is worth noting that, according to a recent bibliometric study regarding the distribution of the biological applications of cyclodextrins, a significant share (around 20%) of these items concern the antimicrobial activity, just behind the antioxidant activity [ 79 ].…”
Section: Incorporation Of Active Substances In Polymeric Matrix Composites For Active Packaging Applicationsmentioning
confidence: 99%